Effectiveness of an mHealth-based impact exercise program for bone health in postmenopausal women: a randomised controlled trial protocol - Borja Sañudo; Gonzalo Reverte-Pagola; Carol Maher; Job Godino; Luis Carrasco; Miguel Ángel Oviedo; Adrián Feria; Horacio Sánchez-Trigo; Hugo Gamboa; Raquel Domingo-Molina; Alejandro Sánchez-Arteaga; Miguel Ángel Giráldez; et al. (BMC Public Health)
Abstract Background Osteoporosis, a major global health concern, increases fracture risk due to reduced bone mineral density (BMD), particularly in postmenopausal women. Weight-bearing and high-impact exercises are recommended for bone health, yet accurately quantifying mechanical loading outside the laboratory remains a challenge. Without precise tools, it is difficult to assess whether individuals engage in sufficient osteogenic activity. Moreover, poor adherence to structured exercise programs limits their effectiveness. Mobile health (mHealth) technologies offer a promising solution by enabling real-time mechanical loading monitoring in free-living conditions and providing personalized feedback to improve adherence. This study evaluates the effectiveness of an individualized mHealth-based intervention in optimizing exercise adherence and promoting bone health in postmenopausal women through real-time quantification of mechanical loading. Methods A single-blind randomized controlled trial (RCT) will include 120 postmenopausal women (≤ 10 years since menopause, < 150 min/week of moderate-to-vigorous physical activity). Participants will be randomly assigned (1:1) to an intervention group (mHealth-based impact exercise program) or a control group (usual care). The 9-month intervention will use wearable activity monitors (Fitbit Versa 3) to track step cadence, impact frequency, and intensity. Exercise targets include fast walking (≥ 100 steps/min), progressive jump training (≥ 3.9 G impact forces), and wrist wall strikes for radius bone adaptation. Primary outcomes include changes in BMD (DXA) at the lumbar spine, proximal femur, and distal radius. Secondary outcomes include bone geometry, and bone turnover markers (β-CTX, P1 NP). Functional mobility, muscle strength, physical activity levels, quality of life and adherence will also be assessed. Discussion This study will provide insights into optimal mechanical loading for osteoporosis prevention and assess the feasibility of mHealth solutions for improving adherence to osteogenic exercise programs. Findings may inform future guidelines on digital health applications for musculoskeletal health. Trial registration: NCT06741956.